FOREIGN EXPERIENCE IN EVALUATING THE EFFICIENCY OF FOOD PROCESSING CLUSTERS (International Congress on Economics, Management and Business Studies, 2026)
Food processing clusters have become an important mechanism for enhancing agricultural competitiveness, increasing value-added production, and ensuring food security in many countries. The effectiveness of such clusters depends on the level of cooperation among participants, technological advancement, innovation capacity, and market integration. This paper examines international experience in evaluating the efficiency of food processing clusters and analyzes the methodologies applied in developed and developing countries. The study identifies key performance indicators, existing challenges in cluster assessment, and practical recommendations for improving evaluation systems. The findings may contribute to the development of effective assessment mechanisms for food processing clusters in Uzbekistan and other emerging economies.
Keywords: food processing cluster, cluster efficiency, performance evaluation, international experience, competitiveness, innovation, agro-industrial development, value chain, food industry, cluster management.